Gambaran Fungsi Diastolik Ventrikel Kiri Pada Penderita Keganasan Yang Mendapat Kemoterapi Doxorubicin - Januar Wibawa Martha; Sunarya Surianata; Amiliana M Soesanto (The Indonesian Heart Association, 2007)
Background. Doxorubicin is one of the first-line chemoterapy against many form of neoplasm but the use is hampered by its cardiotoxic poten-tial with the end result of congestive heart failure. It is imperative that specific monitoring scheme is applied to detect as early as possible the cardiac damage due to doxorubicin. There is large body of evidence that left ventricular diastolic dysfunction precede systolic dysfunction. There-fore, diastolic function may serve as am early monitoring parameter in patients receiving doxorubicin. This study is aimed to delineate the preva-lence of diastolic dysfunction among patients receiving doxorubicin, to define the lowest cumulative dosage of doxorubicin that already cause di-astolic dysfunction, and to describe the association between cumulative dosage of doxorubicin with grade of diastolic dysfunction.Methods. This study utilizes cross sectional design, conducted in Depart-ment of Cardiology and Vascular Medicine to 38 cancer patients receiving doxorubicin in Subdivision of Hematology-Oncology Department of Inter-nal Medicine, Faculty of Medicine, Padjadjaran University. The study com-menced from September 2006 until January 2007.Results. The prevalence of diastolic dysfunction among patients who re-ceived doxorubicin is 86,8%. The actual lowest cumulative dose of doxoru-bicin that already had diastolic dysfunction is 112 mg/m2 but the crossing point between correlation line and the occurrence of E/A ratio and Em/Am ratio of less than 1 is between 110-130 mg/m2. There is negative correlation between cumulative dose of doxorubicin and E/A ratio (r = -0,62) and Em/Am ratio (r = -0,69). Cumulative dose of doxorubicin among normal dias-tolic function, grade 1 diastolic dysfunction and grade 2 diastolic dysfunction are 101,4 + 3,9 mg/m2 , 168,3 + 7,6 mg/m2 and 237,1 + 11 mg/m2, respec-tively (p < 0,01). There is positive correlation between cumulative dose of doxorubicin with grade of diastolic dysfunction (r = 0,7)Conclusions. The prevalence of diastolic dysfunction among patients who received doxorubicin is 86,8%. The lowest cumulative dose of doxorubi-cin that already had diastolic dysfunction is between 110-130 mg/m2 . There is a strong positive correlation between cumulative dose of doxorubicin with grade of diastolic dysfunction.